1976
DOI: 10.1097/00000658-197610000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Gastric, Biliary and Colonic Surgery

Abstract: Antibiotic prophylaxis for surgery has appeared indicated whenever likelihood of infection is great or consequences of such are catastrophic. For better clarification, a prospective, randomized, double-blind study was run on 400 patients undergoing elective gastric, biliary, and colonic operations. There were four treatment categories, with antibiotic being instituted 12 hours preoperatively, just prior to operation, after operation, or not at all. During operation, samples of blood, viscera, muscle, and fat w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
0
10

Year Published

1979
1979
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(166 citation statements)
references
References 9 publications
7
149
0
10
Order By: Relevance
“…29 ' 30 Inappropriate SAP was one of the factors that increased the risk of SSI in this study. When the first antibiotic dose was administered while or after the incision was made, the risk of SSI was significantly higher than when it was administered within 30 minutes before the incision was made (OR, 3.00 [95% CI, 1.09-8.23]).…”
Section: Discussionmentioning
confidence: 64%
“…29 ' 30 Inappropriate SAP was one of the factors that increased the risk of SSI in this study. When the first antibiotic dose was administered while or after the incision was made, the risk of SSI was significantly higher than when it was administered within 30 minutes before the incision was made (OR, 3.00 [95% CI, 1.09-8.23]).…”
Section: Discussionmentioning
confidence: 64%
“…Almost 50 years have passed since the publication of the now historic studies by Polk (1969), Nichols (1973), Stone (1976) and Condon (1979) [1][2][3][4], on the efficacy of perioperative antibiotic use for the prevention of surgical site infections (SSIs, infections of the operative incision and/or operative space) in elective surgery. Subsequent reports by the same authors, as well as by other surgeons and infectious disease specialists, largely confirmed the original findings, thus rendering perioperative antibiotic use an integral part of the contemporary standard of care, as described in clinical practice guidelines published by multiple scientific societies, national and international health organizations [5,6].…”
Section: Editorialmentioning
confidence: 99%
“…[1][2][3][4][5][6] Various risk factors for incisional SSI have been reported, including obesity, emergency operations, and poor glucose control. [7][8][9][10][11] Obesity has been identified as a risk factor for infections and wound complications after a wide variety of surgical procedures.…”
Section: S Urgical Site Infection (Ssi) Including Wound Infection (Imentioning
confidence: 99%